Rural and agricultural subsidies in Latin America: Development costs of misallocated public resources. (17th October 2019) - Anríquez, Gustavo; Foster, William; Ortega, Jorge
Abstract: Motivation: The tendency of governments to surrender to interest groups and divert resources to agricultural subsidies calls into question the efficiency of rural public spending as a tool to promote agricultural growth and rural development: the displacement of government expenditures on public goods by subsidies to private goods hinders farm sector performance. Purpose: This uses an expanded dataset of rural and agricultural spending in Latin America to examine the effect of the composition of government expenditures on rural wellbeing. Furthermore, the article tests whether it is the composition of rural spending more generally or spending on agriculture specifically which drives these impacts. Approach and methods: Econometric panel data methods are used to assess and quantify the relationship between the composition of rural and agricultural spending and sectoral performance. Additionally, the article tests and corrects for the endogeneity of the examined policies and agricultural performance. Findings: The results show that the composition of agricultural expenditures significantly impacts the sector's evolution. We confirm that diverting taxpayer funds from public goods to subsidies decreases farm sector performance. Policy implications: Large gains are to be had from a redistribution of rural (and particularly agricultural) spending from subsidies to public goods. Without addressing this misallocations, the argument to promote rural spending and reduce urban bias in government policies is undermined.